2014
DOI: 10.3746/pnf.2014.19.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinium uliginosum L. Improves Amyloid β Protein-Induced Learning and Memory Impairment in Alzheimer's Disease in Mice

Abstract: The present study investigated the effects of Vaccinium uliginosum L. (bilberry) on the learning and memory impairments induced by amyloid-β protein (AβP) 1-42. ICR Swiss mice were divided into 4 groups: the control (Aβ40-1A), control with 5% bilberry group (Aβ40-1B), amyloid β protein 1-42 treated group (Aβ1-42A), and Aβ1-42 with 5% bilberry group (Aβ1-42B). The control was treated with amyloid β-protein 40-1 for placebo effect, and Alzheimer’s disease (AD) group was treated with amyloid β-protein 1-42. Amylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The present study investigated the neuroprotective effects of EEVC. Despite there being various studies on the effects of V. corymbosum extracts on learning (15,31) and memory (32,33), our study focused on the cognitive changes with regard to aluminium-induced neurodegeneration and haloperidol-induced catalepsy (mechanism of AlCl 3 ). Memory impairment was significant after the exposure of AlCl 3 to the mice, and it induced impaired performance in all the three behavioural parameters, including OFT, Y-Maze test and traction test.…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the neuroprotective effects of EEVC. Despite there being various studies on the effects of V. corymbosum extracts on learning (15,31) and memory (32,33), our study focused on the cognitive changes with regard to aluminium-induced neurodegeneration and haloperidol-induced catalepsy (mechanism of AlCl 3 ). Memory impairment was significant after the exposure of AlCl 3 to the mice, and it induced impaired performance in all the three behavioural parameters, including OFT, Y-Maze test and traction test.…”
Section: Discussionmentioning
confidence: 99%
“…Extract of V. uliginosum partially preserved the outer nuclear layer of retina after light damage [ 19 ]. Another study reported the positive effect of V. uliginosum extract on improving learning and memory impairment in murine Alzheimer’s disease model [ 38 ]. The symptoms of dry eye disease and asthenopia partially overlap [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by degeneration of neurons in specific brain regions, mainly the hippocampus. Consequently, leads to a clinical picture of progressive loss of memory and impairments in cognitive functions (Choi et al, 2014).…”
Section: Alzheimermentioning
confidence: 99%